A closed class? Powers to appoint further beneficiaries as a constraint on the rule in Saunders v Vautier. Issue 9 (30th August 2021) - Johnson, Jeremy; Halligan, Jordan
Abstract: One constraint on the rule in Saunders v Vautier is that, where the trusts include discretionary trusts, the class of beneficiaries must be closed, so it is possible to determine who may legitimately benefit from, and thereby terminate, the trusts. At common law, it is unclear whether a power to appoint further beneficiaries may therefore frustrate the operation of the rule. This article examines the provisions of the Trusts Act 2019 (New Zealand) in the context of a recent decision of the courts in Guernsey, which suggests that the Act may have inadvertently altered the common law position.